Acardiac twins: A Case Report (Journal of Kathmandu Medical College, 2014)
Acardiac anomaly is a rare complication of multiple pregnancy. We report a case at Kathmandu Medical College Teaching Hospital. A 23-year-old multigravida was diagnosed on ultrasonography as having monochorionic monoamniotic twin pregnancy with polyhydramnios and one malformed dead foetus at 18 weeks of gestation. Hence, induction of labor was considered at 36 weeks of gestation. She delivered a macerated male (twin A). Twin B was acardiac with the upper portion consisting of a soft globular mass, the head and upper extremities were absent. The placenta was single. Autopsy revealed absence of heart in twin B. DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10922  Journal of Kathmandu Medical College Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, Page: 34-37